Students’ Perceptions and Experiences of Internal Examinations - Nyaupane, Netra Prasad (Baneshwor Campus Journal of Academia, 2025)
This study examines the undergraduate students’ perceptions and experiences towards internal examinations. The study uses an exploratory research design with a quantitative approach. The data of the study were collected using a stratified random sampling. The total number of respondents of the study is 123 students from Humanities, Management, and Education faculties. It excludes the first-year students. Alignment with board examination standards, clear assessment criteria, efficient exam management, scheduling and contribution to learning are considered as the key components of this study. The findings show that the different groups exhibit identical knowledge of internal examinations. But the male and Management students exhibit relatively favorable knowledge to these exams. The male and second year students have a positive and significant perception towards internal examinations. In the faculty wise analysis of the result, the students of all faculties show stable perceptions. The second year students have more favourable perception and experiences. The findings reveal that there is moderate satisfaction towards internal examinations among students in an overall satisfaction analysis. The second year and Management students exhibit the highest satisfaction levels. This research also pinpoints some areas of improvement. The exam transparency and proper exam management are the main suggestions, which need to be improved. By this, the students’ satisfaction and learning will be more favorable.